Hipomineralização molar-incisivo em escolares da rede municipalde ensino da área urbana e rural de Manaus-AM - Medina, Pollyanna Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
With the purpose of identifying the relationship between dental caries and possible etiologic factors, prevalence, severity of molar-incisor hypomineralization (MIH), 1,124 schoolchildren from rural and urban area in Manaus, Amazonas, were examined. We used the criteria established EAPD and to diagnose MIH and the DMFT and deft indices to diagnose dental caries. A semi-structured questionnaire was completed by the mothers to investigate gestational health and the child's health during the first years of life, as well as the socioeconomic and demographic factors. Data were tabulated and analyzed using descriptive statistics and the chi-square test, Mann-Whitney test, backward method, and odds ratio were used to correlate the variables. The prevalence of MIH in Manaus was 8.9%, not being related to housing area, gender or age of the children diagnosed (p>0,05). Dental alteration was more frequently observed in the lower arch and the first molars were the most affected. The most frequent diagnosis was mild severity. Dental caries experience was higher in rural areas, but in Urban area there was a close relationship between this and the HMI. No association was observed among MIH, socioeconomic factors, and the medical history of the mother, however, a significant association was found among prematurity (p = 0.01), jaundice or lack of oxygen after birth (p = 0.04). MIH is a severe problem for both the children affected and the health professionals due to the complex signs and symptoms, requiring prospective studies to elucidate the etiology.

Com o objetivo de identificar a prevalência, severidade, relação com a cárie dentária e possíveis fatores etiológicos envolvidos na Hipomineralização Molar - Incisivo, foram examinados 1124 escolares da área rural e urbana de Manaus/Am. Para diagnóstico da HMI utilizou-se critérios da EAPD e para cárie dentária, CPOD e ceod. Um questionário semi-estruturado foi respondido pelas mães para investigação da saúde gestacional e da criança nos primeiros anos de vida, fatores socioeconômicos e demográficos. Os dados foram tabulados e analisados por meio de estatística descritiva, associação entre as variáveis pelo teste Qui-quadrado, Mann-Whitney, método backward e Odds ratio. A prevalência da HMI em Manaus foi de 8,9%, não sendo observada diferença relacionada à zona de moradia, gênero ou idade nas crianças diagnosticadas (p>0,05). A alteração dentária estudada foi observada com maior frequência no arco inferior sendo os primeiros molares os mais afetados. A severidade leve foi o diagnóstico mais frequente. A experiência de cárie foi maior na zona rural e na Zona urbana observou-se estreita relação entre esta e HMI. Nenhuma associação foi observada entre HMI, fatores socioeconômicos e história médica da mãe, no entanto, observou-se associação significativa com prematuridade (p= 0,01), icterícia/falta de oxigênio pós-parto (p=0,04). A HMI apresenta-se como grave problema para as crianças afetadas e profissional de saúde, devido à complexidade dos sinais e sintomas apresentados, sendo necessária realização de estudos prospectivos para elucidação da etiologia.
Keywords: Epidemiologia; Cárie dentária; Desmineralização do dente; Tooth demineralization